The left brachiocephalic vein 'spur': A cadaveric and contrast computed tomography study. (December 2019) - Mitsuoka, Hiroki; Naito, Munekazu; Ohmichi, Yusuke; Hagihara, Makiyo; Umemoto, Kanae; Sugimoto, Ikuo; Nakano, Takashi; Ishibashi, Hiroyuki
Objectives: This study investigated the presence of the 'spur' which separates the lumen in the left brachiocephalic vein (LBV). Method: We macroscopically observed the lumen of the bilateral brachiocephalic veins and the superior vena cava in 56 cadavers. The samples were treated with haematoxylin and eosin staining and immunostaining using an α-smooth muscle action antibody. Contrast-enhanced computed tomography images from 170 subjects were analysed. Results: The septal structure was found in only 7% of LBVs included in the cadaveric study and 1.2% of LBVs included in the contrast-enhanced computed tomography image analysis. In the cadaveric study, the septal structure was identified as a 'spur' using histopathology. In both studies, a non-septal structure was found in the right brachiocephalic vein. Conclusions: This is the first report indicating the existence of an LBV 'spur'.